Silica sulfuric acid promoted one-pot synthesis of benzo[4,5]imidazo[1,2-a]pyrimidine derivatives under solvent-free conditions - Chunguang Yang; Fulin Yan; Liqiang Wu (Bulletin of the Chemical Society of Ethiopia, 2010)
A simple and efficient synthesis of benzo[4,5]imidazo[1,2-α]pyrimidine derivatives has been accomplished by the reaction of 2-aminobenzimidazole, aldehydes and β-dicarbonyl compounds under solvent-free conditions in the presence of silica sulfuric acid.